Charles Bukowski’s Online Reading Community: Safeguarding the Author’s Work by Building a Consensus - Amélie Macaud (Sillages Critiques)
This article is a study of a lively online reading community focusing on mid-twentieth century Californian writer Charles Bukowski. For several years, this community of readers, whose behaviors and actions can be compared to that of fans, has tried to right the wrongs of an issue relating to the editing of Charles Bukowski’s posthumous work. They share the belief that John Martin, Charles Bukowski’s former publisher, heavily edited his poems after his death, to the point of making them unrecognizable. An analysis of this forum – more particularly through a close reading of a fourteen-page long discussion thread – will therefore highlight how this community received the posthumous work of their author, slowly but surely managing to build a consensus through the forging of a common enemy.